MANAGEMENT OF ELLIS FRACTURE CLASS III ON 11 WITH PULPECTOMY AND CORE CROWN RESTORATION : PENATALAKSANAAN FRAKTUR ELLIS KELAS III 11 DENGAN PULPEKTOMI DAN RESTORASI MAHKOTA PASAK - I Gusti Ayu Fienna Novianthi Sidiartha; Putu Wiswananta Parama (Interdental Jurnal Kedokteran Gigi (IJKG), 2020)
Introduction: A 19-year-old male patient came to Unud Hospital with a complaint that his upper right front tooth was broken. Case: The patient's right front tooth aches when he consumes cold food or drinks and bleeds every morning. Pain still exists even if food or cold drinks are removed. Complaints felt since 7 months ago. The tooth now feels pain but is not as severe as the initial tooth fracture. Patients have consumed mefenamic acid to reduce the pain. The tooth has never been treated by a dentist. Case management: The patient treated with pulpectomy accompanied by a fused to metal porcelain jacket crown restoration with a cast post core. After controlling for one week after treatment, the desired result is the loss of subjective and objective complaints in the patient. Conclusion: Custom dowel crown restoration post pulpectomy has a high success rate in Ellis Class III fractures of a central incisor with good retention and resistance to both vertical and horizontal pressure.